2009
DOI: 10.1111/j.1755-148x.2009.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Independent regulation of hair and skin color by two G protein‐coupled pathways

Abstract: Hair color and skin color are frequently coordinated in mammalian species. To explore this, we have studied mutations in two different G protein coupled pathways, each of which affects the darkness of both hair and skin color. In each mouse mutant (Gnaq(Dsk1), Gna11(Dsk7), and Mc1r(e)), we analyzed the melanocyte density and the concentrations of eumelanin (black pigment) and pheomelanin (yellow pigment) in the hair or skin to determine the mechanisms regulating pigmentation. Surprisingly, we discovered that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 49 publications
1
30
0
4
Order By: Relevance
“…Although these intracutaneous pigmentationstimulatory effects of TRH appear to have been lost in human epidermal melanocytes in situ, we demonstrate here that they have been preserved in the human HFPU. Moreover, this underscores the validity of the concept that epidermal and hair melanocytes represent phenotypically and functionally rather distinct sub-populations, which underlie differential controls (Slominski et al, 2004;Plonka et al, 2009;van Raamsdonk et al, 2009;Tobin, 2011).…”
Section: Trh Does Not Stimulate Human Epidermal Melanogenesis In Situmentioning
confidence: 86%
“…Although these intracutaneous pigmentationstimulatory effects of TRH appear to have been lost in human epidermal melanocytes in situ, we demonstrate here that they have been preserved in the human HFPU. Moreover, this underscores the validity of the concept that epidermal and hair melanocytes represent phenotypically and functionally rather distinct sub-populations, which underlie differential controls (Slominski et al, 2004;Plonka et al, 2009;van Raamsdonk et al, 2009;Tobin, 2011).…”
Section: Trh Does Not Stimulate Human Epidermal Melanogenesis In Situmentioning
confidence: 86%
“…Melanin is formed by gene action, gene interaction, and environmental factors (Sturm et al, 2001; Ma et al, 2013). Different coat colors of mammal are formed by mutant or interaction of many genes (Van Raamsdonk et al, 2009; Dong et al, 2012; Haase et al, 2013; Yu et al, 2015). Melanocytes are distributed in the epidermis, dermis and hair follicle.…”
Section: Introductionmentioning
confidence: 99%
“…In studying signal transduction of hair follicle, researchers have mainly focused on the melanocortin receptor 1/protein kinase A (MC1R/PKA) signaling pathways (Våge et al, 2014; Dorshorst et al, 2015), Wnt/β-catenin signaling pathways (Enshell-Seijffersa et al, 2010), mitogen-activated protein kinase signaling pathways (Eriksson et al, 2008; Feng et al, 2014), and other signaling pathways, which are involved the growth and development stages of hair follicles and control the proliferation and differentiation of the hair follicle epithelial cells (Tian and Fan, 2006). Recently, some subunits of G protein-couple signaling pathway have been found to regulate and control coat color formation by mutation (Van Raamsdonk et al, 2004; 2009). As a result, the G protein-couple signaling pathway captures has attracted research attention.…”
Section: Introductionmentioning
confidence: 99%
“…Two relatively large studies (together consisting of over 500 UM patient and 400 controls) detected no significant difference in the frequencies of variants between those with or without UM [53,54]. Interestingly, two genes that are highly mutated in UM, the GNAQ and GNA11 genes, also affect the darkness of both hair and skin color [55,56]. As it has been shown that mutations in the hypermorphic alleles of GNAQ and GNA11 are involved in increased dermal melanin and dark skin in mice, it can be hypothesized that patients with different skin and/or hair color are prone to different somatic GNAQ and GNA11 mutations.…”
Section: Genes Correlated To Um Risk Factorsmentioning
confidence: 97%